PREVALENCE OF HYPERTENSION IN MEDICAL PROFESSIONALS OF SMS, MEDICAL COLLEGE, JAIPUR AND ASSESSING THEIR AWARENESS ABOUT HYPERTENSION AND LIFESTYLE MEASURES TO CURB IT - BHARADWAJ, ANURADHA; RAJ, DILIP; SHARMA, VIKAS (International Journal of Current Pharmaceutical Research, 2025)
Objective: Hypertension presents a significant public health challenge in India, particularly among medical professionals who are notably vulnerable to this condition. Assessing their awareness about hypertension and lifestyle measures is crucial for effective intervention. Methods: This cross-sectional study was conducted at SMS Medical College, Jaipur, involving 220 medical professionals aged 23 to 60 years, including 145 males and 75 females. The study aimed to estimate the prevalence of hypertension, assess knowledge regarding the condition, and gauge awareness of lifestyle interventions to curb it. Results: Among the participants, 45.4% were normotensive, 43.2% had Stage I hypertension, and 11.3% had Stage II hypertension. The prevalence of hypertension was notably higher among those with higher body mass indices (BMI): 70% in the obese category, 56% in the overweight category, and 41.8% in the normal BMI group. Regarding awareness, 85% of the participants had good knowledge about hypertension, and 78% were aware of lifestyle measures to manage it. However, only 60% reported implementing these measures in their daily lives. Conclusion: The study uncovered a high prevalence of hypertension among medical professionals. While awareness about hypertension and lifestyle measures is relatively high, actual implementation is suboptimal. Addressing BMI and promoting the adoption of lifestyle modifications could help mitigate the impact of hypertension within this group.